2016
DOI: 10.1002/aenm.201502183
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Energy‐Density Multiple Redox Semi‐Solid‐Liquid Flow Battery

Abstract: well as safety concerns if/when crossover occurs.Non-aqueous Li-based fl ow batteries utilizing organic redox compounds (e.g., ferrocene-based redox, [ 24,25 ] 2,2,6,6-tetramethylpiperidine-1-oxyl, (TEMPO)-based) [ 8,11 ] as catholytes have been shown an effective approach to increase the power density, [ 24,25 ] cycle life, [ 24,25 ] and energy density of the RFBs. [ 1,6,7,9,24,25 ] However, the low solubility of organic redox compounds has limited further improvement in energy density. Alternatively, a non-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 68 publications
(154 reference statements)
0
84
0
Order By: Relevance
“…On another note, it has been recently revealed that cells adopting catholytes and Li metal anodes could suffer from severe self‐discharge because the reaction products at the cathodes tend to spontaneously react with Li metal. By contrast, the self‐discharge of the present Al−Li hybrid cell barely occurs, for not only are the carrier ions relatively unreactive toward the counter electrodes, but the Al metal in the anode and the FP in the cathode are also physically separated; the AlCl 4 − ‐Al 2 Cl 7 − redox couple does not react with LFP, and similarly, Li ions are inert with respect to the Al metal anode.…”
Section: Resultsmentioning
confidence: 99%
“…On another note, it has been recently revealed that cells adopting catholytes and Li metal anodes could suffer from severe self‐discharge because the reaction products at the cathodes tend to spontaneously react with Li metal. By contrast, the self‐discharge of the present Al−Li hybrid cell barely occurs, for not only are the carrier ions relatively unreactive toward the counter electrodes, but the Al metal in the anode and the FP in the cathode are also physically separated; the AlCl 4 − ‐Al 2 Cl 7 − redox couple does not react with LFP, and similarly, Li ions are inert with respect to the Al metal anode.…”
Section: Resultsmentioning
confidence: 99%
“…There are two main methods to construct a Li–S flow battery. One is to combine S or LiPS with conductive carbon to form a suspension ,,. As the catholyte is a suspension, the dissolution of S as LiPS is no longer an issue and the battery can be charged and discharged to the full potential of the Li–S battery chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The Cui group was the first to demonstrate a proof‐of‐concept semisolid LiPS battery prototype, and several variants by other groups have appeared since . The all‐liquid flow battery was demonstrated by the Wang group using a dissolved LiPS catholyte .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al reported a catholyte containing solid sulfur/carbon composites and liquid lithium iodide (LiI) electrolyte, where the LiI serves as both a Li þ conductor and energy storage active material. 354 This design achieved a high energy density (580 W h L…”
Section: Summary and Perspectivesmentioning
confidence: 99%